Desorption of arsenic (As3+), copper (Cu2+) and mercury (Hg2+) ions from iron modified montmorillonite nanoclay - Agulto, Ariane Michelle D.; De Guzman, Jeanne Ranny B.
Heavy metal contamination from the wastewaters of small scale mining industry poses a serious health risk to human beings and contribute to environmental pollution. Adsorption as a wastewater treatment technology is considered efficient in removing contaminants while having low investment costs. It is also relatively simple in design and operation compared to other techniques. Montmorillonite nanoclay, a good low-cost adsorbent, has the properties in significantly removing heavy metals from water. In this study, iron modified montmorillonite (Fe (III)- MMT) nanoclay synthesized via ion exchange technique will be used to adsorb arsenic, copper and mercury ions from separate solutions at a known concentration. Desorption of these metal ions will be done using hydrochloric acid (HCI) and ethylenediaminetetraacetic acid (EDTA) as eluents at varying concentration at constant contact time and room temperature and initial ion concentration. The extent of removal of the adsorbed metal ions from the Fe(III) MMT will be determined using ICP-OES. The average adsorption of Fe-MMT for As3+, Cu2+, and Hg2+ ions were 58.65%, 95.11%, and 12.27%, respectively. Desorption using HCI and EDTA as eluents were possible for As3+ and Cu2+ ions with 0.1 M HCI and 0.01 M EDTA obtained the highest desorption was inefficient due to formation of stable complexes and hysteresis nature of adsorption of Hg2+. Cu2+ desorption with the use of HCI and EDTA was dominant in the basic condition using 0.1 M EDTA and 0.01 M EDTA.